2012
DOI: 10.1590/s1516-18462012005000071
|View full text |Cite
|
Sign up to set email alerts
|

Evolução fonológica de crianças com desvio fonológico submetidas a diferentes abordagens terapêuticas

Abstract: No Português Brasileiro, aproximadamente entre 4 ou 5 anos de idade, a criança já adquiriu todos os fonemas do sistema fonológico adulto. Porém, este processo nem sempre ocorre de acordo com o esperado, verificando-se afastamentos/desvios na aquisição dos sons da fala. O objetivo deste trabalho foi verificar e comparar a evolução do sistema fonológico de crianças com desvio fonológico submetidos à terapia fonológica, acrescida ou não de estimulação das habilidades práxicas orofaciais. A amostra foi composta po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
1
11
1
Order By: Relevance
“…The AFC (12) and ABFW-Fonologia (13) evaluate phonology in Brazilian Portuguese and are the most widely used instruments in Brazilian research (7,(27)(28)(29) . However, the validity and reliability of these instruments has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The AFC (12) and ABFW-Fonologia (13) evaluate phonology in Brazilian Portuguese and are the most widely used instruments in Brazilian research (7,(27)(28)(29) . However, the validity and reliability of these instruments has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…A study that compared the improvement of the phonological system of children with phonological disorder who were submitted to speech therapy, with or without stimulation of orofacial praxis abilities, found out that only the group treated with praxis abilities of language with phonological therapy acquired all the segments which were absent in phonetic inventory 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Researches (ÁVILA;VIEIRA, 2006, MARINI et al, 2011KESKE-SOARES, 2014, GUBIANI;CARLI;KESKE-SOARES, 2015, FARIAS;CERON et al, 2017) have identified a number of factors that may directly influence the production of speech sounds, as well as in the severity of their disorders, such as the inability to organize the phonological rules of the language, difficulties in orofacial praxical skills, dentofacial deformities, oral breathing, changes in the tone of phonoarticulatory organs and imprecision of articulatory points. Thus, justifying the high prevalence of phonological disorders during childhood development.…”
Section: Introductionmentioning
confidence: 99%